Electricity Market Reforms Economics and Policy Challenges - Belyaev, Lev S.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2011)
With the global demand for energy skyrocketing, over the past twenty years many countries have restructured their electric power industries, typically moving from a regulated monopoly to a competitive market structure. The results of these reforms vary significantly from country to country depending on the market organization model and national conditions. This book examines the restructuring in both developed and developing nations, with particular focus on the United States, Great Britain, China, and Russia, and addresses the problems arising from these transitions. The book also contains a comprehensive analysis of different electricity market models and their compatibility with the properties of electric power systems and country conditions. As the most thorough and up to date analysis of the theory and practical experience of electricity deregulation, this book is a must-read for academics, students and researchers with an interest in electric power industry restructuring. It also has direct relevance for engineers, regulators and other decision makers in companies and governmental agencies concerned with energy issues.
Electric Power Systems, Their Properties and Specific Features -- Electric Power Industry in the Context of Microeconomics -- Models of Electricity Market Organization -- Short Run Productivity Costs and the Electricity Market -- EPS Expansion with Different Market Models -- Foreign Experience in Electric Power Industry Restructuring -- Power Industry Restructuring in Russia.-.
Keywords: Economics; Electric engineering; Development Economics; Economic policy; Economics/Management Science; Economic Policy; R & D/Technology Policy; Energy Technology; Development Economics